Analysis of sedimentation rate in peat lakes: Case study of Lake Teloko, South Sumatera - Dion Awfa; Cheisyha Alfiradina; Muhammad N. Hanif; M. Ridwan A. Aziz; Farhan B. Rozzan; Miftahul H. Genisia; Rifka N. Azizah (Indonesian Journal of Applied Environmental Studies, 2025)
Teloko Lake in Ogan Komering Ilir, South Sumatra, is a peat swamp ecosystem that has undergone revitalization through dredging activities aimed at increasing water storage capacity and reducing flood risk in surrounding areas. This study analyzes post-revitalization sedimentation processes, evaluates water quality conditions, and identifies the characteristics of suspended particles to support effective and adaptive lake management. The main objectives of this research were to determine the spatial distribution of Total Suspended Solids (TSS), quantify sedimentation rates, and examine the relationship between particle properties and hydrological conditions in order to assess the impacts of the revitalization intervention. Sampling was conducted at five representative locations at water depths ranging from 0.68 to 1.30 meters during the dry season in September 2025. The results show that TSS concentrations ranged from 681 to 740 mg/L, with an average value of 710.92 mg/L and a standard deviation of ±9.6%, indicating relatively uniform conditions among sampling sites and suggesting the absence of significant effects from dredging activities. A 72-hour sedimentation test revealed extremely low settling rates, as suspended particles remained in the water column without forming a distinct sediment layer. This behavior is attributed to the dominance of colloidal particles smaller than 20 µm that contain positively charged organic matter, generating repulsive forces that inhibit natural sedimentation processes. Overall, the findings confirm that the intrinsic properties of peat water and ongoing lake dynamics exert a stronger influence on sedimentation behavior than technical revitalization measures. These results provide important insights for long-term lake conservation and management, emphasizing the need for ecological approaches, such as the application of natural coagulants, to improve sediment control and maintain water quality in peat swamp lake ecosystems.